2017
DOI: 10.1177/0272684x17701261
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Attitude and Practices Toward Lassa Fever Control and Prevention Among Residents of Ile-Ife, Southwest Nigeria

Abstract: Lassa fever had been reported as a cause of death especially in endemic parts of Nigeria. This study assessed the knowledge, attitude, and practices toward Lassa fever control and prevention among residents of Ile-Ife, southwest Nigeria. Descriptive cross-sectional study was conducted among consenting randomly selected adults using an interviewer administered questionnaire. Data were analyzed using descriptive and inferential statistics. A total of 400 questionnaires with completed data were analyzed (response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 9 publications
6
15
0
Order By: Relevance
“…This result is comparable to that obtained in Southwest, 10 South South, 16 and North Central Nigeria, 20 In other studies, lower proportions of respondents demonstrated good preventive practices. 18,22,26 From the results of this study, almost equal proportions of respondents had a good knowledge of Lassa fever and showed good preventive practices. This result is different from that of other studies where proportions that demonstrated good preventive practices were higher.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This result is comparable to that obtained in Southwest, 10 South South, 16 and North Central Nigeria, 20 In other studies, lower proportions of respondents demonstrated good preventive practices. 18,22,26 From the results of this study, almost equal proportions of respondents had a good knowledge of Lassa fever and showed good preventive practices. This result is different from that of other studies where proportions that demonstrated good preventive practices were higher.…”
Section: Discussionmentioning
confidence: 72%
“…This result is different from that of other studies where proportions that demonstrated good preventive practices were higher. 16,18,26 This may be an indication that there is a poor understanding of Lassa fever among the population. It has already been observed in Nigeria that there is a weak integration of culture and socio-behavioural prevention measures which could be effective for the prevention of Lassa fever.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that half of the respondents demonstrated a poor knowledge of LF fever symptoms and risk factors. This poor knowledge is worrisome despite the [21]. The finding of a high awareness of LF in this study, is similar to community-based studies in Lafia by Reuben and Gyar [22], and in Irrua by Ochei et al [23] A low community awareness of LF in Owo, Ondo State has been reported by Ilesanmi et al [24] and in Oshogbo by Adebimpe et al [25] Respondents in Abakaliki LGA had a better knowledge of LF risk factors compared to its symptoms suggesting a gap in risk communication information dissemination in the state and the need for risk communication content in the state to contain more LF symptoms for early identification of suspected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Rice is often the stable crop in endemic areas (particularly in western Africa), which is typically grown in fields or low-lying swamps that encourage rodent habitation (50). The challenges presented by the educational and communication infrastructure in endemic regions also prevent optimal disease control, with a recent survey finding that 76% of residents in a Nigerian urban town had inadequate knowledge of Lassa fever and 51% had poor control practices (51). Practices such as hunting rodents for food and for use in sacrificial ceremonies have also been documented to increase risks for infection (50).…”
Section: Disease Transmission and Social Implicationsmentioning
confidence: 99%